PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) TERHADAP KEMAMPUAN SISWA DALAM MENGANALISIS SEJARAH DI SMA MUHAMMADIYAH 1 METRO - Leni Andari; Sumiyatun Sumiyatun (Swarnadwipa, 2018)
This study aims to determine the effect of the use of cooperative learning model type Student Teams Achievement Divisions (STAD) on the ability to analyze the history of class XI science students of Muhammadiyah 1 Metro High School even semester 2017/2018 academic year. This type of research is quasi-experimental with nonequivalent control group design research design. The study population was the entire class XI IPA which consisted of 103 students of Muhammadiyah 1 Metro High School in the even semester and the determination of the sample using cluster random sampling method, the research sample was XI IPA class of 26 students and XI IPA4 totaling 22 students. Based on data analysis the results of hypothesis testing at a significance level of 0.05 using equation two averaged to get sig of 0.02 <0.05, then H0 is rejected and H1 is accepted in other words there is an average difference, the average obtained by the experimental class amounting to 79.50 and the control class obtaining an average of 71.13 with this it can be seen that the experimental class obtains an average higher than the control class with a range of values of 8.37. The conclusion of this study is that there is an effect of cooperative learning model type Student Teams Achievement Divisions (STAD) on the ability to analyze the history of class XI IPA students in Muhammadiyah 1 Metro High School in the academic year 2017/2018.